2018
DOI: 10.20944/preprints201810.0328.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapeutic Microbiology: the Role of <em>Bifidobacterium Breve</em> as Food Supplement for the Prevention/Treatment of Pediatric Diseases

Abstract: The human intestinal microbiota, establishing a symbiotic relationship with the host, plays a significant role for the human health. It is also well known that a disease status is frequently characterized by a dysbiotic condition of the gut. A probiotic treatment can represent an alternative therapy for enteric disorders and human pathologies not apparently linked to the gut environment. Among bifidobacteria, strains of the species Bifidobacterium breve are widely used in pediatrics. B. breve is the dominant s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 137 publications
0
5
0
Order By: Relevance
“…EPS form an interfacial layer separating the bacteria from its surrounding environment, considerably contributing to their anti-pathogenic activity [28]. In animal studies, the administration of B. breve , producing EPS, reduced colonization of Citrobacter rodentium , in comparison with the mutant strain [124,133]. EPS isolated from B. bifidum facilitated the growth of lactobacilli and other anaerobic bacteria and inhibited the growth of enterobacteria, enterococci, and Bacteroides fragilis .…”
Section: Effects Of Probiotics As Heat-killed Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…EPS form an interfacial layer separating the bacteria from its surrounding environment, considerably contributing to their anti-pathogenic activity [28]. In animal studies, the administration of B. breve , producing EPS, reduced colonization of Citrobacter rodentium , in comparison with the mutant strain [124,133]. EPS isolated from B. bifidum facilitated the growth of lactobacilli and other anaerobic bacteria and inhibited the growth of enterobacteria, enterococci, and Bacteroides fragilis .…”
Section: Effects Of Probiotics As Heat-killed Bacteriamentioning
confidence: 99%
“…For this reason, strains of B. breve are widely used in pediatrics, having antimicrobial activity against enteropathogens and immunomodulatory effects. Of note, it is devoid of transmissible antibiotic resistance traits and cytotoxicity [133].…”
Section: Clinical Benefits Of Tyndallized Bacteria As Probiotics Imentioning
confidence: 99%
“…We do not believe that to be the case, given that breastfeeding clearly has a beneficial and multifactorial impact on infant health and development and the results of our logistic regression analysis which indicate that breastfeeding is associated with reduced likelihood of an underweight growth outcome in HEU infants. Second, given the lower relative abundance of Bifidobacterium species in HIV-infected mothers and HEU infants, as well as the presence of antibiotics in the mothers' breast milk, the use of a Bifidobacterium probiotic supplement may be of benefit in these populations (86); however, this approach should be evaluated in a follow-up clinical trial.…”
Section: Stool Samples From Hiv-infected Mothers Exhibited Greater Abundance Ofmentioning
confidence: 99%
“…Notably, B. breve strains are frequently isolated from stool samples of healthy breastfed infants (Collado et al, 2012 ) and milk samples of breastfeeding mothers (Khodayar-Pardo et al, 2014 ), highlighting events of vertical transmission between the mother and her newborn (Milani et al, 2015b ). Furthermore, different studies have highlighted how this species is involved in protection against the development of allergies through its impact on the intestinal epithelial barrier, and in modulating the host's immune system (Inoue et al, 2009 ; Hougee et al, 2010 ; Bozzi Cionci et al, 2018 ). In this regard, a previous study showed the role of B. breve UCC2003 in the proliferative development of the intestinal epithelial cells during early life (Kiu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since B. breve has been incorporated as a functional ingredient in various probiotic supplements (Bozzi Cionci et al, 2018 ), we herein report a genome-based screening aimed at identifying a B. breve prototype of the adult gut. The identified representative B. breve strain, i.e., PRL2012, was subjected to various omics-based evaluations by means of metatranscriptome analyses when co-cultivated with other bacterial species commonly found in the human microbiome, highlighting particular genetic features of PRL2012 that appear to respond to the presence of and/or sustain interactions with other commensal organisms.…”
Section: Introductionmentioning
confidence: 99%